Nilai-Nilai Pendidikan Karakter Menurut Kemendikbud dalam Novel Ranah 3 Warna Karya Ahmad Fuadi - Nurhayati, Nurhayati (Jurnal Pendidikan Dewantara, 2023)
Some of the case of juvenile delinquency often occur in Indonesia, one of them is the case of six vocational school students who were arrested by the police after abusing a grandmother who was known as a person with mental illness. This incident occurred in Panompuan village, Angkola Timur, South Tapanuli, and several other cases of juvenile delinquency. This case occurs because of the lack of character possessed by young people. This research uses a descriptive-qualitative method, using library research as a type of research. According to the Ministry of Education and Culture, there are five values of character education in the novel entitled Ranah 3 Warna by Ahmad Fuadi, namely religious, nationalist, integrity, independence and mutual cooperation. So that young people become good citizens of Indonesia. Alif Fikri, the main character in the novel entitled Ranah 3 Warna, reflects the attitude and character of young people who have big dreams of becoming writers and want to pursue their dreams to get to America. Despite all the economic limitations, it doesn't make Alif discourage his intention. Thanks to the effort and character he has, he can achieve his dream.